Accuracy of various impression materials and methods for two implant systems: An effect size study. Issue 2 (April 2018) - Schmidt, Alexander; Häussling, Teresa; Rehmann, Peter; Schaaf, Heidrun; Wöstmann, Bernd
Abstract: Purpose: An accurate impression is required for implant treatment. The aim of this in-vitro study was to determine the effect size of the impression material/method, implant system and implant angulation on impression transfer precision. Methods: An upper jaw model with three BEGO and three Straumann implants (angulations 0°, 15°, 20°) in the left and right maxilla was used as a reference model. One polyether (Impregum Penta) and two polyvinyl siloxanes (Flexitime Monophase/Aquasil Ultra Monophase) were examined with two impression techniques (open and closed tray). A total of 60 impressions were made. A coordinate measurement machine was used to measure the target variables for 3D-shift, implant axis inclination and implant axis rotation. All the data were subjected to a four-way ANOVA. The effect size (partial eta-squared [ η 2 P ]) was reported. Results: The impression material had a significant influence on the 3D shift and the implant axis inclination deviation ( p -values = .000), and both factors had very large effect sizes (3D-shift [ η 2 P ] = .599; implant axis inclination [ η 2 P ] = .298). Impressions made with polyvinyl siloxane exhibited the highest transfer precision. When the angulation of the implants was larger, more deviations occurred for the implant axis rotational deviation. The implant systems and impression methods showed partially significant variations ( p -values = .001–.639) but only very small effect sizes ( η 2 P = .001–.031). Conclusions: The impression material had the greatest effect size on accuracy in terms of the 3D shift and the implant axis inclination. For multiunit restorations with disparallel implants, polyvinyl siloxane materials should be considered. In addition, the effect size of a multivariate investigation should be reported.